Spatio-temporal Analysis of Land Use and Land Cover Change in Kirtipur Municipality - Sharma, Puspa; Pakhrin, Manita; Giri, Chet Narayan; Linkha, Tika Ram; Gurung, Sher Bahadur (Geographical Journal of Nepal, 2026)
This study examines land use and land cover (LULC) dynamics in Kirtipur Municipality, Nepal, from 2005 to 2025 and analyzes the relationships among parameters influencing built-up expansion. This study used GEE and GIS techniques to process multi-temporal imagery from Google Earth Pro (2005, 2010 and 2015) and Sentinel-2 (2020 and 2025). While GWR evaluated the spatial impact of topography, accessibility, and socioeconomic factors, supervised Random Forest classification and manual digitization were used to create LULC maps. Cultivated land decreased from about 69% to 49%, while built-up areas grew from about 11% to 32%. Waterbodies, shrubland/grass, and forests remained mostly unchanged. Urban growth seemed to be expanded towards flat to gently sloping terrain along the major roads, CBD, and markets. Over time, the direction of expansion shifted from the northern to the southern and southwestern regions. Institutional expansion, population growth, migration, and sociocultural changes were important drivers. The study emphasizes the importance of integrating agricultural land protection with urban planning to ensure sustainable development in Kirtipur Municipality.